Model for the determination of the load carrying capacity of the RC walls - Miskovic, Z. (Computer Assisted Methods in Engineering and Science, 2004)
The paper presents the possibility of the limit stress state approximation of the reinforced concrete wall structures by discontinuous stress fields with variable configuration. Heuristic optimization technique, simulated annealing, is applied to determine optimal configuration for approximation of load carrying capacity based on lower bound theorem of theory of plasticity. Model was tested by comparing with the results of several experimental tested beams, as well as with other numerical models.